PENERAPAN MEDIA PAPAN HITUNG (PAHIT) DALAM PEMBELAJARAN MATEMATIKA PERMULAAN KELAS 2 DI SDN 22 AMPENAN - Anjani, Nurvita Dwi (Al-mujahidah, 2024)
Teaching aids are objects that are used to assist in the process of conveying information, demonstrations, learning tools, or demonstrations of a particular concept or concepts. In this article the author will explain one of the teaching aids, namely, the Calculation Board. A counting board or PAHIT is a teaching aid used to calculate repeated multiplication, division, addition and subtraction materials. Using this counting board can train children to think quickly and more easily understand the concepts of multiplication and division. At the concrete operational age (7-11 years), elementary school age children generally have difficulty understanding abstract mathematics. Therefore, learning media is needed that can provide solutions to increase students' interest in learning. This research uses descriptive qualitative methods through observation, interviews and documentation. This writing aims to develop calculating board learning media as a medium that can help students' understanding of starting calculations in mathematics subjects. Through this multiplication board media, it is hoped that class II students will be able to think actively in understanding the concepts of multiplication and division so that students can improve their mathematics learning outcomes.Key Word : arithmetic concept, counting board media, mathematics.